2018
DOI: 10.1123/jpah.2018-0370
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Physical Activity Among Children and Youth in 9 Countries With Low to Medium Human Development Indices: A Global Matrix 3.0 Paper

Abstract: Background: This study compares results of physical activity report cards from 9 countries with low to medium human development indices, participating in the Global Matrix 3.0 initiative. Methods: Country-specific report cards were informed by relevant data and government policy documents, reporting on 10 core indicators of physical activity for children and youth. Data were synthesized by report card working groups following a harmonized process. Grade assignments for each indicator utilized a standard gradin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 67 publications
2
32
1
Order By: Relevance
“…Ethiopian children are in a lifestyle shift toward physical inactivity [10][11][12]. Evidence suggests that childhood inactivity has contributed to the rise in obesity in many developing countries including Ethiopia [13]. A systematic review conducted on overweight/obesity among children and adolescents in Ethiopia found that the combined prevalence of overweight and obesity among children was 11.3% (overweight = 8.9%, obesity = 2.4%).…”
Section: Key Pointsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ethiopian children are in a lifestyle shift toward physical inactivity [10][11][12]. Evidence suggests that childhood inactivity has contributed to the rise in obesity in many developing countries including Ethiopia [13]. A systematic review conducted on overweight/obesity among children and adolescents in Ethiopia found that the combined prevalence of overweight and obesity among children was 11.3% (overweight = 8.9%, obesity = 2.4%).…”
Section: Key Pointsmentioning
confidence: 99%
“…Active play % of children and youth who participated in unstructured active play for several hours a day [6,13] 2018…”
Section: Year Of Publicationmentioning
confidence: 99%
See 3 more Smart Citations